Pengaruh Pembagian Kerja dan Worklife Balance TerhadapEfektivitas Kerja Dimediasi oleh Job Satisfaction - Manalu, Regista; Ardiani, Winda; Putra, Rizky (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to determine the effect of division of labor and work-life balance on work effectiveness, with job sastisfaction as a mediator, on employees of PT Toyota Auto 2000 Medan Amplas. Path analysis research design is used as an analytical tool to determine the direction of the variables studied and see how significant the influence of the independent variable is with the dependent either directly or indirectly through the mediating variable. This research uses a quantitative approach with descriptive methods. In this study the entire population was sampled, namely 102 employees of PT Toyota Auto 2000 Medan Amplas. The results of this study indicate that division of labor does not have a direct effect on work effectiveness (β=0.006; t=0.070; p=0.944), nor does work-life balance (β=0.116; t=1.841; p>0.05). However, job division significantly affects job satisfaction (β=0.236; t=3.328; p=0.001), and work-life balance has a stronger influence on job satisfaction (β=0.554; t=6.672; p=0.000). Job satisfaction was found to have a significant effect on work effectiveness (β=0.763; t=10.626; p=0.000). Mediation analysis shows that job satisfaction mediates the relationship between work distribution and work effectiveness (β=0.180; t=2.929; p=0.004) and work-life balance and work effectiveness (β=0.423; t=6.487; p=0.001). This research is expected to contribute to the development of more effective human resource management policies and strategies to increase employee job satisfaction and productivity in the automotive industry.